Estimating water content of unsaturated sandy soils by GPR during a drainage experiment. Issue 1 (February 2021) - Zhang, M. H.; Bano, M.; Feng, X.; Lesparre, N.; Girard, J. F.; Razakarisoa, O.; Belfort, B.; Lehmann, F.; Friedmann, P.
Abstract: This study shows how to estimate water content of unsaturated sandy soils from ground-penetrating radar (GPR) data acquired during water drainage experiment. Using the Topp equation, water content can be converted to dielectric permittivity. Afterwards, based on 1D forward modeling method a GPR synthetic trace is generated. Finally, a trial-and-error match of modeled and observed GPR traces was performed to estimate the optimum set of parameters characterizing the materials composing the soil. According to the comparison of the modeling signal and the real signal, we go back to update the water content. Repeating the procedure until the modeling signal fits the real signal very well. We used this procedure to obtain the evolution of water content of unsaturated sandy soils. The method is presented on drainage experiment carried out on unsaturated sandy soil of a large-controlled experimental site. In order to follow the change of the water level, we measured GPR profiles at different times and picked up four GPR profiles, then the same trace (No. 700) were picked up on each GPR profile and estimated the water content from each signal.